Dooyweerd on Law and Morality: Legal Ethics - A Test Case - Cameron, Alan (Victoria University of Wellington Law Review, 1998)
The philosophical work of the Dutch Christian intellectual Hernum Dooyeweerd is not internationally well known. His major jurisprudential work is even less well known owing to the fact that it has not been published either in his native language or in English. The author of this article, who is involved in the editing of the English translation of Dooyeweerd’s jurisprudence for publication, briefly expounds the main themes and some of the basic concepts of his legal philosophy with reference to the general problem of the relationship between law and morality and then attempts to apply these insights towards a theoretical elucidation of the relationship between law and legal ethics. Central to the Dooyeweerdian jurisprudential perspective is a highly original theory of the modal aspects. ln particular, the notions of the jural and ethical aspects provide the baszs of his unique account of the relationshzp between law and morality and of this article’s application of Dooyeweerd’s theoretical framework to the topic of legal ethics.